Innovating south-south cooperation : policies, challenges, and prospects - Besada, Hany; Tok, M. Evren; Polonenko, Leah McMillan, 1982- (Studies in international development and globalization., 2019)
"The evolving aid architecture and mounting development challenges caused by recent food, financial and energy crises, demand an urgent and critical review of existing aid modalities, policy-making and forums for international cooperation. In light of the rise of emerging powers, an important question is the extent to which the changing global order is transforming the nature of development cooperation. Promoting equitable broad-based economic growth leading to poverty alleviation requires new understanding of what constitutes development assistance, good governance, transparency, ownership, and accountability. The future of SSC depends on many factors, such as improved means of communication and sharing of knowledge among partner countries, adopting a more analytical approach to define regional and global public goods, identifying good and bad practices and evaluating them, and improving transparency, merging economic and social priorities. Using a variety of case studies, this book provides novel approaches for furthering SSC on a global scale, to establish more effective public policies in the area of international development."--